The Role of Genomic Sequencing in Diabetes Mellitus - Yanne Pradwi Efendi; Alexander Kam; Eva Decroli; Dinda Aprilia; Syafril Syahbuddin (Scientific Journal, 2025)
Diabetes Mellitus is a chronic metabolic disorder caused by impaired insulin secretion and/or insulin resistance. Genetic testing through genomic sequencing is one of the modalities available for diabetes mellitus. Genomic sequencing is the process of analysing DNA obtained from a blood sample (or alternatively from tissue samples). Broadly, genomic sequencing plays two major roles in diabetes mellitus: supporting diagnosis and guiding therapeutic approaches. In its development, genomic sequencing has proven valuable for diagnostic investigation in type 1 diabetes and maturity-onset diabetes of the young (MODY), as well as for assessing the polygenic risk score (PRS) in type 2 diabetes. Establishing a definitive diagnosis allows for the selection of individualised therapy. Several randomised controlled trials have demonstrated that the risk of developing diabetes can be reduced by up to half if detected at an earlier stage. Moreover, genomic sequencing can identify genetic variants that influence responsiveness to antidiabetic treatments. At present, several potential antidiabetic agents targeting novel pathways are under development and in various stages of clinical trials. The application of genomic sequencing thus facilitates the implementation of individualised therapy, ultimately contributing to the realisation of precision medicine.